RESPONSIBLE SELF-CARE – THE FUNDAMENTAL PRINCIPLES AND PLACE IN THE MODERN RUSSIAN HEALTHCARE SYSTEM - S. N. Tolpygina; S. Yu. Martsevich; A. V. Kontsevaya; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
An increase in the prevalence of chronic noncommunicable diseases is a significant problem for both patients and the health system. According to the World Health Organization "Promoting effective responsible self-care ... is essential to reduce the financial burden on health systems". The term "responsible self-care" means "self-help" and "self-care". The concept of responsible self-care is to create conditions and prerequisites for forming a responsible attitude to own health, children's and family's health by maintaining a healthy lifestyle, wider and more competent use of over-the-counter medication for the prevention or self-care of the trifling ailment and chronic non-communicable diseases, continuing the therapy prescribed by the doctor. Changes in the legislative framework, coordinated activity of medical workers of various levels and specialties, as well as improvement of medical literacy of the population are necessary for the implementation of the practice of responsible self-care in Russia. Promotion of healthy lifestyles and the personal responsibility of people for their health in the media and Internet resources, self-monitoring of the status and basic health indicators, increasing adherence of patients to prescribed medicines for the treatment of chronic diseases based on gained medical know-ledge, skills and habits are the most applicable measures for Russia to date.